Diseño y elaboración de la imagen corporativa de la empresa Certicol S.A.S. (2018)
During the investigation, the issue of establishing a corporate image for the company Certicol SAS was addressed, with the purpose of establishing a relationship of greater knowledge with the companies that use their services in the field of electrical installations, in the Department of Valle del Cauca and in Colombia